2004
DOI: 10.1007/978-3-540-30539-2_24
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between XL and Gröbner Basis Algorithms

Abstract: Abstract. This paper compares the XL algorithm with known Gröbner basis algorithms. We show that to solve a system of algebraic equations via the XL algorithm is equivalent to calculate the reduced Gröbner basis of the ideal associated with the system. Moreover we show that the XL algorithm is also a Gröbner basis algorithm which can be represented as a redundant variant of a Gröbner basis algorithm F4. Then we compare these algorithms on semi-regular sequences, which correspond, in conjecture, to almost all p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 19 publications
0
59
0
3
Order By: Relevance
“…According to (2), each element ofṼ can be written as a sum of {x k g } 1≤k, ≤n . Now let AṼ ∈ M n 2 ×n 2 (K) be a matrix associated to the linear transformation Vect {x k g } 1≤k, ≤n →Ṽ .…”
Section: Theorem 5 Let M (D) Be the Set Of Monomials Of Degree D ≥mentioning
confidence: 99%
“…According to (2), each element ofṼ can be written as a sum of {x k g } 1≤k, ≤n . Now let AṼ ∈ M n 2 ×n 2 (K) be a matrix associated to the linear transformation Vect {x k g } 1≤k, ≤n →Ṽ .…”
Section: Theorem 5 Let M (D) Be the Set Of Monomials Of Degree D ≥mentioning
confidence: 99%
“…Although not fully understood when first introduced, currently there seems to be a much better understanding of the behaviour of the XL algorithm, including its merits and limitations [1,2,3,4,12]. In particular it has been shown that some of the heuristics used in deriving the complexity of the XL algorithm [8] were too optimistic [12].…”
Section: Linearization Methodsmentioning
confidence: 99%
“…[3] for an overview of the idea. Although it has been shown that techniques from the XL-family are strictly less efficient than from the F-family [40,39,5,17], XL does have its merits as it is easier to adapt to different settings. Hence we have used a specialized version of XL in our solver to improve its efficiency, cf.…”
Section: Related Workmentioning
confidence: 99%